Biomechanical analysis of different lifting speeds when using an active exoskeleton - Mayer, Dominik; Siebert, Tobias; Hasenmaier, Jens; Stutzig, Norman (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMusculoskeletal disorders (MSDs), especially lower back pain, are common consequences of repetitive and long-term mechanical stress. Exoskeletons offer a promising approach to reduce this stress by supporting the wearer during physical labour. This study investigated the effect of an active exoskeleton (Apogee) on muscle activation and joint kinematics during load lifting at different lifting speeds and exoskeleton support levels.MethodsSixteen healthy young adults (8 male, 8 female) lifted a 15 kg box at two lifting speeds (9 and 12 lifting cycles/min) and four support levels: 1) without exoskeleton, 2) exoskeleton in passive mode, 3) 50% support and 20% counterforce, 4) 100% support and 60% counterforce. Muscle activity was measured in the M. erector spinae (MES), M. biceps femoris (MBF) and M. vastus medialis (MVM) using EMG. Furthermore, joint range of motion (ROM) in the ankle, knee and hip were analysed using 3D motion capture.ResultsFaster lifting significantly (p < 0.05) increased MBF (by 4.0% ± 1.5% maximum voluntary contraction, MVC) and MVM (1.6% ± 0.7% MVC) activity, while MES remained unaffected. The highest support level led to a significant decrease in MES and MBF activity by about 22.3% MVC and 10.6% MVC, respectively, as well as a small increase in hip joint ROM by 6° compared to lifting without exoskeleton support. There was no interaction between the level of support and lifting speed.DiscussionThe decrease in MES activity of 22.3% MVC with full support suggests a potent reduction in spinal load. MBF activity increased less with higher speeds when support was applied. The MVM showed low and stable activity across all conditions. These findings suggest that the active exoskeleton Apogee provides support regardless of lifting speed and may help prevent MSDs in occupational settings. Users can adjust support levels based on task requirements and personal comfort.